2016
DOI: 10.1111/cdoe.12233
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to dental amalgam and pregnancy outcome

Abstract: We found no evidence for serious perinatal consequences of maternal exposure to amalgam fillings during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
2
9
1
Order By: Relevance
“…The results reported here corroborate previous studies that showed no association between birth weight or birth length and maternal seafood consumption [ 99 , 100 , 101 , 102 ] or the number of dental amalgams [ 87 , 103 ]. Two controlled clinical trials examining the health effects of amalgam conducted in children—the New England Children’s Amalgam Trial (NECAT) [ 104 ] and the Casa Pia study [ 105 ]—reported no evidence of adverse psychosocial outcomes from Hg exposure in children.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results reported here corroborate previous studies that showed no association between birth weight or birth length and maternal seafood consumption [ 99 , 100 , 101 , 102 ] or the number of dental amalgams [ 87 , 103 ]. Two controlled clinical trials examining the health effects of amalgam conducted in children—the New England Children’s Amalgam Trial (NECAT) [ 104 ] and the Casa Pia study [ 105 ]—reported no evidence of adverse psychosocial outcomes from Hg exposure in children.…”
Section: Discussionsupporting
confidence: 92%
“…To this end, amalgam fillings have been the subject of an ongoing dispute for centuries, known as “amalgam wars”, due to concern of health effects of released Hg [ 1 , 4 , 5 , 13 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. The number of amalgam fillings is associated with Hg concentrations in the adult brain and urine, and has a tendency to be associated with Hg in the fetal kidney (but not in the fetal brain), amniotic fluid, cord blood/serum, and/or placenta [ 29 , 32 , 63 , 83 , 84 , 85 , 86 ], though no associations have been found with fetal biometric measurements [ 77 , 78 , 87 ]. A recent Avon Longitudinal Study of Parents and Children (ALSPAC) study reported that women with four or more dental amalgams at the beginning of pregnancy had higher Hg blood levels [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adjustment for potential confounders changed the risk estimate slightly, but it was still statistically significant after adjustment. The results are consistent with those from analyses of the same cohort regarding stillbirth [25]. In the present study both stillbirths and deaths in the first week after birth were included.…”
Section: Discussionsupporting
confidence: 91%
“…An increased risk of miscarriage in dental personnel with moderate and high occupational exposure to amalgam was found in a Finnish study [23], and higher frequency than expected of spontaneous abortion and perinatal mortality was reported in a study of female dentists [24]. In a previous study of pregnancy outcomes related to dental amalgam exposure in the Norwegian Mother and Child Cohort Study (MoBa), the adjusted odds ratio (OR) for stillbirth was 1.38 (95%CI 0.80 to 2.39; p = 0.13) for mothers in the highest exposure group (9 or more teeth filled with dental amalgam) [25]. However, since the exposure variable was included as a categorical variable and not as a continuous variable, the power of the analysis was limited [26].…”
Section: Introductionmentioning
confidence: 99%
“…Differently, in some regions of the world such as China, MeHg exposure via a rice-based diet is an increasing risk factor [29]. A pathway of concern for pregnant women is also represented by Hg vapors released from maternal dental amalgams, which may contain up to 50% of elemental Hg [41], and, particularly among women living in developing nations, by Hg vapors released during mining activity. During pregnancy, maternal exposure to Hg could produce damage on neurodevelopmental systems such as behavioral, cognitive patterns and motor skills, and on the immune and reproduction systems, noticeable later in life [7].…”
Section: Sources Of Exposurementioning
confidence: 99%